When Is Humiliation More Intense? The Role of Audience Laughter and Threats to the Self - Mann, Liesbeth; Feddes, Allard R.; Leiser, Anne; Doosje, Bertjan; Fischer, Agneta H. (Frontiers in Psychology, 2017)
In personal accounts, humiliation is often reported as a very intense, painful, negative emotion. We report two scenario studies in which we explored two factors that may contribute to the intense character of humiliation: (1) unwanted, negative public exposure, and (2) a threat to central aspects of one’s identity. Study 1 (N = 115) assessed emotional reactions to a public insult when an audience responded with either laughter or not and when someone from the audience offered support after the insult or no support was offered. Results showed that the intensity of humiliation increased when people laughed after the insult. However, support offered after the insult had no effect on reported humiliation. Study 2 (N = 99) focused on threats to different self-related values and showed stronger reports of humiliation when central self-related values were threatened than when less central self-related values were threatened. Study 2 also replicated the audience-effect from Study 1, but only when central self-related values were threatened and not when less central self-related values were threatened. Limitations of these studies (e.g., the use of scenarios) and potential avenues for future research, such as the (long-term) consequences of humiliation and humiliation in the context of social media, are discussed.